Local Government Finance : a report of the committee of inquiry presented to Parliament by the Secretary of State for the Environment, the Secretary of State for Scotland and the Secretary of State for Wales. - Report of Committee of Enquiry; Layfiel, F. (London: Her Majesty's Stationery Office, 1976)
This publication is a review of local government finance in England, Scotland and Wales including recommendations by a committee of inquiry.
aia 18/02/19
Loans
Keywords: Local finance; Local government; United Kingdom